Analysis of prognostic factors affecting immune checkpoint inhibitor therapy in tumor patients exposed to antibiotics - Chen, Qian; Zhang, Zhen; Li, Xiaoli; Feng, Shaomei; Liu, Shui (Frontiers in Oncology, 2023)
Objective: Meta-analysis was performed to evaluate the prognostic factors in tumor patients treated with immune checkpoint inhibitors (ICIs) under antibiotic exposure. Method: Literature on the effect of antibiotics on the prognosis of tumor patients receiving ICIs was retrieved from Pubmed, Cochrane Library, EMbase, EBSCO Evidence-Based medicine database, China Biomedical Literature Database (CBM), and China National Knowledge Network (CNKI), and relevant influencing factors were extracted. Meta-analysis of efficacy was performed using RevMan 5.4 software. Results: A total of 9 studies for 1677 patients were included. Meta-analysis results showed that in terms of progression-free survival, gender (male vs female), eastern cooperative oncology group performance status (ECOG PS) (1-2 vs 0), history of another cancer (Yes vs No), liver metastasis (Yes vs No), antibiotics (within previous 2 months), PD-L1 (1%-49%), and PD-L1 (≥ 50%) factors are associated with PFS in patients treated with ICIs under antibiotic exposure. In terms of overall survival, gender(male vs female), ECOG score (1-2 vs 0), history of another cancer (Yes vs No), brain metastasis(Yes vs No), liver Metastasis (Yes vs No), radiation (within previous 3 months), antibiotics (within previous 2 months), PD-L1 (1%-49%), and PD-L1 (≥ 50%) factors are associated with OS in patients with antibiotic exposure receiving ICIs for tumor treatment. Conclusions: Gender, ECOG score, history of another cancer, brain metastasis, liver metastasis, radiation (within previous 3 months), antibiotics (within previous 2 months), PD-L1 (1%-49%), and PD-L1 (≥ 50%) were associated with clinical benefit in patients with antibiotic exposure receiving ICIs for tumor treatment. Based on the above factors, clinicians can screen cancer patients who receive ICIs under antibiotic exposure and rationally use antibiotics and ICIs in combination.